Total Synthesis of the Humulene‐Derived Sesquiterpenoid (‐)‐Integrifolian‐1,5‐dione - Anne Zimmer; Prof. Alois Fürstner (ChemistryEurope)
Abstract The oxygenated sesquiterpenoid (‐)‐integrifolian‐1,5‐dione, which originates from a plant that finds widespread use in South American traditional medicine, is distinguished by a rigid bicyclic framework consisting of a cyclopropane that is cis‐annulated to a cyclodecane ring. The first total synthesis of this demanding target is described, which relies on a highly selective cyclopropanation reaction of an α‐stannylated‐α‐diazoester catalyzed by a heteroleptic dirhodium paddlewheel complex, followed by an unprecedented Stille‐type cross coupling of the resulting stannylated cyclopropane with methyl iodide as the electrophilic partner to form the all‐carbon quaternary stereocenter at one of the bridgehead positions. Equally decisive was the bicyclization strategy based on lactonization/ring expansion that ultimately allowed the strained ten‐membered carbocycle to be forged.